2D–3D Digital Image Correlation Comparative Analysis for Indentation Process. - Bermudo-Gamboa, Carolina; Martín-Béjar, Sergio; Trujillo-Vilches, Francisco Javier; Castillo-López, Germán; Sevilla-Hurtado, Lorenzo (MDPI, 2019)
Nowadays, localized forming operations, such as incremental forming processes, are being developed as an alternative to conventional machining or forming techniques. An indentation process is the main action that takes places in these forming activities, allowing small, localized deformations. It is essential to have the knowledge of the material behavior under the punch and the transmitted forces to achieve correct control of the entire procedure. This paper presents the work carried out with the digital image correlation (DIC) technique applied to the study of the material flow that takes place under an indentation process. The material flow analysis is performed under 2D and 3D conditions, establishing the methodology for the calibration and implementation for each alternative. Two-dimensional DIC has been proven to be a satisfactory technique compared with the 3D method, showing results in good agreement with experimental tests and models developed by the finite element method. Notwithstanding, part of the indented material flows under the punch, emerging on the front surface and generating a dead zone that can only be addressed with a 3D technique. So, the main objective is to carry out a comparison between the 2D and 3D techniques to identify if the 3D application could be mandatory for this type of process. Also, a 2D–3D mix analysis is proposed for study cases in which it is necessary to know the material flow in that specific area of the workpiece.
Keywords: Método de los elementos finitos; Procesado de imágenes - Técnicas digitales; Digital image correlation; Indentation process; Incremental forming; Finite element method; Material flow